PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP DISIPLIN KERJA GURU DI SMP NEGERI 11 PRABUMULIH - Rusnita Rusnita; Yasir Arafat; Mulyadi Mulyadi (STKIP Pesisir Selatan, 2021)
This study aims to determine and describe the effect of principal leadership and teacher work motivation together on the work discipline of teachers at SMP Negeri 11 Prabumulih. This study uses a quantitative method with a correlational approach (cause and effect). Data were analyzed using multiple linear regression analysis. The research got the conclusion (1) There is an effect of the principal's leadership on the work discipline of teachers at SMP Negeri 11 Prabumulih. (2) There is an effect of teacher work motivation on teacher work discipline at SMP Negeri 11 Prabumulih. (3) There is an influence of the leadership of the principal and the work motivation of teachers together on the work discipline of teachers at SMP Negeri 11 Prabumulih